Effects of Collaborative Assessment on Undergraduate Students Writing Performance - Taufiqulloh Taufiqulloh; Fahrus Zaman Fadhly; Ihda Rosdiana (Universitas Syiah Kuala, 2024)
This study investigates the impact of collaborative assessment on undergraduate students writing performance in English as a Foreign Language (EFL) courses in Indonesia. Collaborative assessment, which encompasses self-assessment, peer assessment, and teacher assessment, enhances writing proficiency and critical thinking skills. This study exclusively incorporates the field dependence-independence (FDI) cognitive styles to explore how these learning styles interact with collaborative assessment strategies. The research used a quantitative method to involve 120 students from Universitas Pancasakti Tegal, divided into field-independent and field-dependent groups. Over 14 weeks, students participated in collaborative assessment activities within their writing courses. Pre- and post-tests, along with survey questionnaires, measured improvements in writing performance and student attitudes. Results indicated significant improvements in writing skills for both cognitive style groups, with field-independent students showing slightly higher gains. The study concludes that collaborative assessment effectively enhances writing performance and fosters positive learning attitudes, regardless of cognitive style, and recommends integrating this approach into EFL writing instruction. The findings imply that collaborative assessment is a valuable tool for accommodating diverse learning styles in EFL education.